The Evidential Power of Notarial Deeds in Land Disputes between Certificate Owners and Land Cultivators - Cahyadi, Arvin Bintang; Hasibuan, Muhammad Reza Afdilla; Samosir, Tetti (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
This study aims to analyze the evidentiary power of notarial deeds in land disputes between certificate owners and land cultivators. Notarial deeds are authentic evidence that legally have perfect evidentiary power, especially when they form the basis for the transfer of registered land rights. However, in practice, there are often clashes between the strength of administrative evidence and physical control by the cultivator. This study uses normative and empirical legal methods with a qualitative approach. Data were obtained through literature studies, document studies, and analysis of court decisions. The results of the study indicate that although notarial deeds and certificates provide a strong legal standing for the owner, the judge’s considerations also include aspects of physical control, good faith, and other supporting evidence. Legal protection for certificate owners can be optimally realized if accompanied by real control and active legal action in defending rights. Therefore, the presence of notarial deeds needs to be understood not only as administrative documents, but also as part of the evidentiary system that must be supported by facts in the field.